2017
DOI: 10.3390/antiox7010003
|View full text |Cite
|
Sign up to set email alerts
|

Natural Nanoparticles: A Particular Matter Inspired by Nature

Abstract: During the last couple of decades, the rapidly advancing field of nanotechnology has produced a wide palette of nanomaterials, most of which are considered as “synthetic” and, among the wider public, are often met with a certain suspicion. Despite the technological sophistication behind many of these materials, “nano” does not always equate with “artificial”. Indeed, nature itself is an excellent nanotechnologist. It provides us with a range of fine particles, from inorganic ash, soot, sulfur and mineral parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
79
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(82 citation statements)
references
References 138 publications
0
79
0
3
Order By: Relevance
“…In recent studies by Griffin et al it was shown that various plant materials can be rendered into nanosized particles by using a combination of high speed stirring (HSS) and high pressure homogenization techniques (HPH) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Diminution of plant materials to sizes < 10 µm means that all plant cells, which typically possess sizes > 10 µm, are destroyed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent studies by Griffin et al it was shown that various plant materials can be rendered into nanosized particles by using a combination of high speed stirring (HSS) and high pressure homogenization techniques (HPH) [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Diminution of plant materials to sizes < 10 µm means that all plant cells, which typically possess sizes > 10 µm, are destroyed.…”
Section: Introductionmentioning
confidence: 99%
“…The equipment required is low-cost, freely available and meanwhile established in many laboratories world-wide [ 10 , 11 , 12 , 13 , 14 ]. The feasibility of the PlantCrystal technology was proven in previous studies, where PlantCrystals were shown to increase the antimicrobial and antifungal activity of various plant materials [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Their feasibility to improve antioxidative capacity has not yet been investigated and a systematic study investigating the influence of plant material and process parameters on PlantCrystal size and properties is also not yet available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now possible to produce nanoparticles of the relevant plant materials with comparable ease, for instance by milling or fermentation. These nanosized materials are entirely "natural" as far as their chemical composition is concerned, and often exhibit an amazing release profile for active ingredients and therefore also considerable biological activity [11][12][13][14]. Nanosized plant materials rich in biologically active ingredients may therefore unlock the considerable potential of many food items, and possibly also of materials which so far have been considered as "waste", such as the spent coffee ground, grape seeds and various shells, leftovers and peels [15].…”
mentioning
confidence: 99%
“…The naturally occurring nanoparticles include volcanic ash soot from forest fires or diesel engines [3][4][5][6]. These naturally occurring nanomaterials are usually physically and chemically heterogeneous [7]. On the other hand, engineered nano-materials (ENMs) are created by the manipulation of matter at the nano-scale to produce new materials and structures [8,9].…”
Section: Introduction Engineered Nanomaterials (Enms)mentioning
confidence: 99%